2020
DOI: 10.3390/coatings10100940
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Reverse Roll Coating of Non-Isothermal Magnetohydrodynamics Viscoplastic Fluid

Abstract: This article describes the development of a mathematical model of the reverse roll coating of a thin film for an incompressible non-isothermal magnetohydrodynamics (MHD) viscoplastic fluid as it passes through a small gap between two rolls rotating reversely. The equations of motion required for the fluid added to the web are constructed and simplified using the lubrication approximation theory (LAT). Analytical results are obtained for the velocity profile, pressure gradient, and temperature distribution. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…e innovation of the effort is inspired by the necessity from the coating manufacturing to uniform thin, faster, and coat stable layers, by coating rheology and operating coater operating conditions. e theoretical study of reverse roll coating of non-isothermal, an incompressible, magnetohydrodynamic viscoplastic fluid has been deliberated by Ali et al [39]. e governing equation of flow added to the sheet in the basic form was achieved by employing the technique of lubrication approximation.…”
Section: Introductionmentioning
confidence: 99%
“…e innovation of the effort is inspired by the necessity from the coating manufacturing to uniform thin, faster, and coat stable layers, by coating rheology and operating coater operating conditions. e theoretical study of reverse roll coating of non-isothermal, an incompressible, magnetohydrodynamic viscoplastic fluid has been deliberated by Ali et al [39]. e governing equation of flow added to the sheet in the basic form was achieved by employing the technique of lubrication approximation.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of China's national strategic goal of "Carbon Peak" and "Carbon neutral", in recent years, it has attracted extensive attention and has been developed [1]. However, in terms of the coating materials in practical applications, it is found that in the roller-coating process, due to the influence of the temperature, viscosity, roller speed, vibration stability, and other factors of the coating, the coating material will form bubbles on the surface of the steel plate, resulting in defects on the surface of the coating, and some parameters for the stability of the coating material have to be evaluated before a coating implementation [2]. Therefore, a test equipment is needed to evaluate the roll coating performance of coating materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, great devotion has been devoted to the study of several non-Newtonian fluid models as a single constitutive expression, which is not suitable for representing the relationship between stress and shear rates of different fluids. Researchers are currently very interested in non-Newtonian fluid models and have been examined in a variety of contexts (Ali et al, 2020;Azam, 2022a;Ali et al, 2022;Azam et al, 2022;Azam, 2022b). The Eyring-Powell material model has several advantages: 1) it is a model based on the kinetic theory; 2) it describes the characteristics of shear-thinning fluids; and 3) the characteristics of Newtonian materials can be recovered for high shear rates.…”
Section: Introductionmentioning
confidence: 99%